(untitled) (Research, Society and Development, 2024)
Introduction: Preservation of deciduous teeth in the dental arch is essential for the development of the stomatognathic system. The use of chloramphenicol, tetracycline, and zinc oxide-eugenol (CTZ) paste for the treatment of deciduous teeth dispenses with the need for instrumentation of the canals and allows completion in a single session. Objectives: To evaluate the effectiveness of CTZ paste in the treatment of deciduous teeth with irreversible pulp damage. Methods: An integrative literature review of a qualitative and exploratory nature, searching electronic platforms according to the descriptors (DeCs): "deciduous tooth" and “endodontic” and “Chloramfenicol”, in English and Portuguese, from 2014 to 2024. Results and discussion: The authors summarize that CTZ paste is a viable option, considering the complex root anatomy, physiological root resorption, and lack of cooperation from the child. The technique of sterilization of pulp tissue lesions and repair – LSTR uses antibiotic paste in the mouth of the canals and on the floor of the pulp chamber of deciduous teeth without prior chemical-mechanical preparation and creates a sterile zone that is biocompatible with the exfoliative process. The combination of antimicrobial drugs in the paste is successful in clinical and radiographic monitoring. However, tetracycline causes staining of the crown, causing aesthetic damage, requiring caution in the rehabilitation of anterior teeth. Final considerations: CTZ paste is an alternative for the treatment of teeth with irreversible pulp damage in pediatric dentistry, with satisfactory clinical success rates and radiographic results, although additional studies with larger samples and long term results are needed to better elucidate the scientific evidence.